2014
DOI: 10.2337/dc13-2762
|View full text |Cite
|
Sign up to set email alerts
|

Canagliflozin Provides Durable Glycemic Improvements and Body Weight Reduction Over 104 Weeks Versus Glimepiride in Patients With Type 2 Diabetes on Metformin: A Randomized, Double-Blind, Phase 3 Study

Abstract: OBJECTIVETo assess the efficacy/safety of canagliflozin, a sodium-glucose cotransporter 2 inhibitor, compared with glimepiride over 104 weeks in patients with type 2 diabetes inadequately controlled with metformin. RESEARCH DESIGN AND METHODSIn this randomized, double-blind study, patients (N = 1,450) received canagliflozin 100 or 300 mg or glimepiride (titrated up to 6 or 8 mg/day) during a 52-week core period followed by a 52-week extension. RESULTSAt week 104, reductions from baseline in A1C were 20.65%, 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

34
278
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(314 citation statements)
references
References 31 publications
34
278
1
1
Order By: Relevance
“…11, 12, 22, 23, 24, 25, 26, 27, 28, 29, 30 For cardiovascular outcomes analysis, 3 RCTs11, 12, 22 and 2 observational studies23, 24 were included with 351 476 patients and median follow‐up of 3.1 years. Nine RCTs contributed to the analysis of long‐term noncardiovascular safety and efficacy of SGLT2 inhibitors, with a medium follow‐up of 2 years 11, 12, 22, 25, 26, 27, 28, 29, 30. All trials were carried out with patients who had type 2 DM.…”
Section: Resultsmentioning
confidence: 99%
“…11, 12, 22, 23, 24, 25, 26, 27, 28, 29, 30 For cardiovascular outcomes analysis, 3 RCTs11, 12, 22 and 2 observational studies23, 24 were included with 351 476 patients and median follow‐up of 3.1 years. Nine RCTs contributed to the analysis of long‐term noncardiovascular safety and efficacy of SGLT2 inhibitors, with a medium follow‐up of 2 years 11, 12, 22, 25, 26, 27, 28, 29, 30. All trials were carried out with patients who had type 2 DM.…”
Section: Resultsmentioning
confidence: 99%
“…Data were sorted by first author, year of publication, country of the study, design, age range of the participants, total sample size, SGLT2 inhibitor, comparator, number of patients, dosage, and follow‐up duration (Table 1). 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55 …”
Section: Methodsmentioning
confidence: 99%
“…While the insulin‐independent mechanism of canagliflozin leads to a low inherent risk of hypoglycaemia, the mild osmotic diuresis it causes may be associated with an increased risk of volume–depletion events, including dehydration. Across Phase 3 studies in a broad range of patients, canagliflozin provided reductions in HbA1c, body weight, and systolic blood pressure (BP) and was generally well tolerated, with a low risk of hypoglycaemia when not used in conjunction with insulin or sulphonylureas 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22. An analysis of T2DM patients living in hot climates found that canagliflozin treatment was generally well tolerated, with a low incidence of volume depletion–related AEs 23…”
Section: Introductionmentioning
confidence: 99%